Effect of the artificial rain on the efficiency of dormancy break treatment in apple trees - Palladini, Luiz Antonio; Petri, José Luiz (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this work was to evaluate the influence of the time between the treatment application to the dormancy break and the artificial rain on the bud burst in young apple (Malus domestica Borkh) trees. The experiment was carried out with potted Gala apple samplings during 1992 and 1993. The treatments included application of the chemicals mineral oil (MO) and hydrogenated cyanamide (HC) for dormancy break, associated or not with an artificial rain of 25 mm applied during 45 minutes. The artificial rain was applied just after the spray with MO plus HC, at 0.5, 1, 2, 4, 8, and 24 hours. In both years, the treatment for breaking the dormancy without rain resulted in the highest (60.7%) effect on bud burst. Among the treatments that received artificial rain, the lowest bud burst was observed when the rain was applied just after the application of the dormancy break treatment. However, there were no significant differences on bud burst among the treatments exposed to the artificial rain from 30 minutes after spraying MO plus HC, which indicates that the chemical treatment does not need to be reapplied under these circumstances.